Europe in the digital age: regulating digital finance without suffocating innovation. Issue 2 (3rd July 2021) - Pavlidis, Georgios
ABSTRACT: The expansion of the cryptocurrency market in the last 10 years has been exponential and a 'watch and wait strategy' towards the regulation of crypto-assets is no longer appropriate and justifiable. Opportunely, the European Union (EU) has recognised the need for a digital finance strategy to address regulatory gaps and help relaunch and modernise the European economy in the aftermath of the COVID-19 pandemic. The philosophy behind the EU Digital Finance Strategy, in particular the proposed Regulation on Markets in Crypto-Assets (MiCA) and the proposed Digital Operational Resilience Act (DORA), is innovation-friendly. The EU legislative initiatives seek to unlock the potential of crypto-assets while mitigating the risks to financial stability, market integrity and consumer protection. This will lead to additional and better financial products for consumers, improving financial inclusion and financing of businesses.